Design Performance Measurement of Intelligent Garbage Sorting Cart using Neutrosophic Sets and SuperHyperSoft - Yiyue Zhang (Neutrosophic Sets and Systems)
With the rapid increase in urban waste generation, efficient and automated waste sorting solutions have become essential for sustainable waste management. This study evaluates the gent Garbage Sorting Cart under the decision-making methodology. We use the Quadripartitioned Single-Valued Neutrosophic Z-Numbers (QSVNZN) with four membership functions to dela with the uncertainty information. Two methods are used in this study, such as the CRITIC method to compute the criteria weights and the ARAS method to rank the alternatives. The decision-making process is used with the SuperHyperSoft set to deal with different criteria and alternatives. We used eight criteria and six alternatives. We proposed six collections of SuperHyperSoft. In each collection, we applied the ARAS methodology and ranked the alternatives. The results show stability in the ranks.